The Influence of Decision-Making Quality on Perceptions of Foreign Grant Accountability - Nisfatul Izzah; Bhenu Artha (Journal of Business and Management Review, 2021)
The Indonesian government and other non-profit organizations have received many foreign grants, one of which is the Global Fund AIDS Tuberculosis and Malaria (GFATM) grant. As the recipient of the Sub Recipient TB Care 'Aisyiyah grant, East Java has an absolute obligation to account for the funds received. One of its obligations is to present accountable financial statements. However, achieving accountability is not easy. There is a long process with strict terms and conditions from donors. These terms and conditions make institutions and financial statement providers sometimes feel bored and accountability more difficult to realize. Factors of human resources, tasks, and the environment are the benchmarks for an accountant of foreign grants to have a strong perception of the importance of accountability. This study aims to determine the perception of accountants in assessing the accountability of financial statements as an expense or an asset. A qualitative method was used with an emphasis on interviews. The findings showed that the accountability of the financial statements of foreign grants was assessed as intangible assets because the recipients could benefit from the grants financially and non-financially. The finance staff benefited from the accounting field as well as general knowledge about tuberculosis and extensive networking in various sectors.